Kinetic Analysis of the Reaction between Tannic Acid (TA) and L-Lysine Diisocyanate (LDI) Systems - Ali Karbasi; Reza Darvishi; AmirHossein Enayati Gerdroodbar; Ghasem Payam (International Journal of Polymer Science)
The kinetics of the synthesis of green polyurethane from the reaction between tannic acid (TA) and L-lysine diisocyanate (LDI) were investigated using the differential scanning calorimeter (DSC) technique and dynamic rheological tests. The evaluation of the reaction behavior of the prepared samples was carried out using nonisothermal conditions at dynamic heating rates of 5, 10, 15, and 20°C/min. The evolution of the activation energy with conversion was computed through the five isoconversional methods of Ozawa-Flynn-Wall and Kissinger-Akahira-Sunose (KAS), the Ozawa-Flynn-Wall method (OFW), Friedman (FR), Starink, and Vyazovkin. The average activation energy calculated from these methods was estimated at 46.5, 46.8, 47.2, 47.3, and 51.4 KJ/mol, respectively. The preexponential factor was evaluated at 5.04×105 1/s. The overall reaction order (n+m) was also found to be around 1.8912. The results of the combination of the model-free method and model-fitting approach exhibited that the reaction mechanism was an autocatalytic type, implying the autocatalytic effect of the urethane groups formed during the reaction. The obtained kinetic for TA/LDI was verified through its good agreement with the experimental data. Moreover, the results found from the isothermal rheological test show that with increasing temperature, the gelation time decreases.